Spiritual resilience: Understanding the protection and promotion of well-being in the later life - Manning, Lydia (Journal of religion, spirituality & aging, 2019)
Spirituality is important to a large percentage of the older adult population and serves as a key factor of resilience. Using qualitative research, we conducted and analyzed interviews with 64 participants willing to discuss their experiences with adversity. Participants ranged in age from 52 to 93 with a mean age of 74. For the purposes of this study, we analyzed 46 of the 64 interviews, selecting participants who indicated that spirituality was an important resource for managing hardship. The researchers examined the connections between spirituality and resilience. Using in-depth interviews, we explored the interplay between spirituality and resilience and the importance spirituality plays in dealing with adversity and hardship. A grounded theory analysis of the 46 interviews was performed. Major findings include participants' use of spirituality as a tool to promote and maintain resilience in late life in five key domains: reliance on relationships, spiritual transformation, spiritual coping, power of belief, and commitment to spiritual values and practices. Results are presented as an interpretation of the participants' perceptions of their spirituality, and indicate their reliance on spirituality to overcome hardship. In addition, we discuss the connections between spirituality and resilience and how these connections play out in the lives of older adults when considering their generational and cohort status. The roles these two constructs play in the lives of older adults are considered.